Evaluasi Aktifitas Belajar Mahasiswa Berbasis Teknologi Informasi Pada Masa Pandemi Covid 19 di Fakultas Teknik Universitas Batanghari Jambi - Venny Yusiana; Eko Suprapto (Universitas Batanghari Jambi, 2021)
Information technology is an information service that is used as a form of interaction used by students during the COVID-19 pandemic. One of them as a medium of learning or communication. This study using quantitative methods that are analytical observational through the distribution of questionnaires through a google form. The distribution of the sample was 323 respondents with a research design in the form of a cross-sectional study approach. The results of data analysis based on univariate stated that 50.8% of respondents stated that learning dared to support learning activities but did not experience a significant increase, while bivariate analysis of information technology supported Unbari students' interactions with learning activities. during the covid 19 pandemic.